2016
DOI: 10.1213/ane.0000000000001434
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Simulation to Teach Anesthetists’ Non-Technical Skills in Rwanda

Abstract: Rwandan anesthesia providers show improvement in ANTS practice during cesarean delivery after 1 teaching session using a low-cost high psychological fidelity simulation model with debriefing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…A recent study showed that a lowcost and low physical fidelity mannequin was effective in teaching NTS to Rwandan anesthesia providers. 25 Our study will hopefully provide useful information to help guide the development of future simulation scenarios intended to teach NTS in centres with limited financial resources.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study showed that a lowcost and low physical fidelity mannequin was effective in teaching NTS to Rwandan anesthesia providers. 25 Our study will hopefully provide useful information to help guide the development of future simulation scenarios intended to teach NTS in centres with limited financial resources.…”
Section: Discussionmentioning
confidence: 97%
“…Previous literature determining ANTS scores for anaesthesia trainees working in low-resource settings assessed during simulation showed that the average mean difference between scores was 2 and a standard deviation of the mean difference of 3.1 (SMD¼0.645). 13 Assuming a two-tailed test with a¼0.05, 90% power, an effect size of SMD¼0.645, 10% dropout, and a worst-case scenario for the parent distribution (i.e. minimum asymptotic relative efficiency), 32 participants were required.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous studies showing that targeted training can improve the participants' non-technical skills. 13,23 We investigated the impact of VAST soon after its development and implementation. It contributes new knowledge regarding simulation training and non-technical skills retention in low-resource settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations